Vital Statistics: Summary of a Workshop - Council, National Research; Education, Division of Behavioral and Social Sciences and; Statistics, Committee on National; Cork, Daniel L; Siri, Michael J (National Academies Press, 2013)
Vital statistics, the records of birth and death, are a critical national information resource for understanding public health. Over the past few decades, the specific program that gathers the data has evolved into a complex cooperative program between the federal and state governments for social measurement. The Vital Statistics Cooperative Program (VSCP) is currently maintained by the National Center for Health Statistics (NCHS). The U.S. vital statistics system relies on the original information reported by myriad individuals, channeled through varying state and local information systems, and coordinated and processed by a federal statistical agency that has experienced relatively flat funding for many years. The challenges facing the vital statistics system and the continuing importance of the resulting data make it an important topic for examination. A workshop, held by the National Academies and summarized in this volume, considered the importance of adequate vital statistics. In particular, the workshop assessed both current and emerging uses of the data, considered the methodological and organizational features of compiling vital data, and identified possible visions for the vital statistics program.